Intraperitoneal Nigella sativa for Prevention of Postoperative Intra-Abdominal Adhesions in Rats. (1st December 2014) - Karatas, Ahmet; Ozlu, Tulay; Ozyalvacli, Gulzade; Tosun, Mehmet; Cetinkaya, Ayhan; Donmez, Melahat Emine; Turker, Arzu; Bayrakdar, Husna
ABSTRACT Objective: To evaluate intraperitoneal administration of Nigella sativa (NS) to prevent postoperative intraperitoneal adhesion (PPA) after surgical manipulation of rat uterine horn. Materials and Methods: Two forms of NS were used in the study (Volatile oil (NSVO) and the ethanolic extract (NSEE)). A total of 50 rats were randomly assigned to the sham group (n = 10), control group (n = 10), NSVO group (n = 10), NSEE group (n = 10), and the Seprafilm group(n = 10). After 14 days, rats were sacrificed. Adhesions were examined macroscopically, and degree of adhesions was scored. A part of horn was excised, and superoxide dismutase (SOD) and glutathione peroxidase activities as well as malondialdehyde levels were evaluated, and histological score was calculated. Results: Total microscopic score of the NSEE group was significantly lower than the control group (p = .001) and was marginally significantly lower than the seprafilm group (p = .005). Collagen formation score was higher in the seprafilm group compared to the sham and NSEE groups (p < 0.001, p = .003, respectively). Apoptotic cells were lower in the NSEE group compared to the control group (p = .003) and also lower in the NSEE and NSVO groups compared to the seprafilm group (p = .001, p < .001, respectively). Only SOD activity was higher in the NSVO and seprafilm groups compared to the control group (p < .001). Conclusion: NSEE form seems to have a possible effect in the prevention of PPAs. This may occur by its effect in decreasing collagen formation and by decreasing apoptosis in the injured tissues. NSVO form seems to induce SOD. Therefore, combined use of NSVO with seprafilm may increase the adhesion preventive effect of seprafilm.